Modular and Chemoselective Strategy for Accessing (Distinct) α, α‐Dihaloketones from Weinreb Amides and Dihalomethyllithiums. Issue 22 (20th October 2020) - Touqeer, Saad; Senatore, Raffaele; Malik, Monika; Urban, Ernst; Pace, Vittorio
Abstract: The selective transfer of diversely functionalized dihalomethyllithiums (LiCHBrCl, LiCHClI, LiCHBrI, LiCHCl2, LiCHBr2, LiCHFI) to Weinreb amides for preparing gem‐ dihaloketones in one synthetic operation is reported. The capability of these amides as acylating agents and, the wide availability of dihalomethanes as pronucleophiles, enable a straightforward route to the title compounds under full chemocontrol. No racemization phenomena were evidenced in the case of optically active materials. Additionally, tolerance to sensitive functional groups (esters, amides, halogens, olefins etc .) was uniformly noticed, thus making this conceptually intuitive strategy flexible and tunable by the operator. Abstract :